Managers’ Motives behind the Quality of Segment Disclosure - Abbas, Ahmad (Jordan Journal of Business Administration, 2025)
This research underlines two perspectives to scrutinize the managers’ motives on the quality of segment disclosure. From the agency perspective, this research aims to find the effect of cost made by managers as the part of agency motive in disclosing information related to the business segment, while from the signaling perspective, this research also seeks to find the effect of business diversification as a signal to determine the disclosure quality of the segment. The sample included public firms listed in Indonesia. The nexus between variables was analyzed using fixed effect model with generalized least squares including cross-section weights and checked using robustness tests. The findings of this research disclose that the effect of cost made by managers is positive on the level of segment disclosure quality. They indicate that managers use the agency motive to improve the quality of the disclosure. The costs made by them through the transfer of funds across segments intend to manage the inefficient segment performances. This research also discloses that managers use business diversification as a signaling motive to spur the quality. In addition, the interplay function between quantity and quality is found. It means that the improved quality of segment disclosure reflects a larger quantity.